Avoiding pitfalls in diagnosing basilar artery occlusive disease: clinical and imaging clues — case report - Conforto, Adriana Bastos; Ciríaco, Jovana Gobbi Marchesi; Yamamoto, Fábio Iuji; Puglia Júnior, Paulo; Leite, Claudia da Costa; Martin, Maria da Graça Morais; Scaff, Milberto (São Paulo Medical Journal, 2010)
CONTEXT: The aim of this paper was to report on the characteristics that aid in establishing the diagnosis of basilar artery occlusive disease (BAOD) among patients with hemiparesis and few or minor symptoms of vertebrobasilar disease. CASE REPORT: This report describes two cases in a public university hospital in São Paulo, Brazil. We present clinical and imaging findings from two patients with hemiparesis and severe BAOD, but without clinically relevant carotid artery disease (CAD). One patient presented transient ischemic attacks consisting of spells of right hemiparesis that became progressively more frequent, up to twice a week. The neurological examination revealed slight right hemiparesis and right homonymous hemianopsia. Magnetic resonance imaging (MRI) revealed pontine and occipital infarcts. Magnetic resonance angiography and digital subtraction angiography revealed severe basilar artery stenosis. The other patient presented sudden left-side hemiparesis and hypoesthesia. One year earlier, she had reported sudden onset of vertigo that, at that time, was attributed to peripheral vestibulopathy and was not further investigated. MRI showed a right-side pontine infarct and an old infarct in the right cerebellar hemisphere. Basilar artery occlusion was diagnosed. Both patients presented their symptoms while receiving aspirin, and became asymptomatic after treatment with warfarin. CONCLUSIONS: Misdiagnosing asymptomatic CAD as the cause of symptoms in BAOD can have disastrous consequences, such as unnecessary carotid endarterectomy and exposure to this surgical risk while failing to offer the best available treatment for BAOD. Clinical and imaging features provided important clues for diagnosis in the cases presented.